1979
DOI: 10.1016/s0006-3495(79)85208-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical reconstruction of the quantal event at nicotinic synapses

Abstract: To test our present quantitative knowledge of nicotinic transmission, we reconstruct the postsynaptic conductance change that results after a presynaptic nerve terminal liberates a quantum of acetylcholine (ACh) into the synaptic cleft. The theory assumes that ACh appears suddenly in the cleft and that is subsequent fate is determined by radial diffusion, by enzymatic hydrolysis, and by binding to receptors. Each receptor has one channel and two ACh binding sites; the channel opens when both sites are occupied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 35 publications
4
127
0
Order By: Relevance
“…This prediction was borne out by their experimental results, using a-bungarotoxin to reduce the effective concentration of ACh receptors (Land et al 1981). In addition, both Land et al (1984) and Wathey et al (1979) (Sakmann, 1978;Jackson, Wong, Morris, Lecar & Christian, 1983 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prediction was borne out by their experimental results, using a-bungarotoxin to reduce the effective concentration of ACh receptors (Land et al 1981). In addition, both Land et al (1984) and Wathey et al (1979) (Sakmann, 1978;Jackson, Wong, Morris, Lecar & Christian, 1983 …”
Section: Methodsmentioning
confidence: 99%
“…Of the many models that have been proposed to simulate synaptic currents (Magleby & Stevens, 1972a;Gage, 1976;Steinbach & Stevens, 1976;Rosenberry, 1979;Wathey, Nass & Lester, 1979;Land, Salpeter & Salpeter, 1980, 1981Land, Harris, Salpeter & Salpeter, 1984;Madsen, Edeson, Lamtt & Milne, 1984;Madsen, Edeson & Milne, 1987), those presented by Land et al (1981Land et al ( , 1984 and Wathey et al (1979) are of particular relevance to the present work, since, in these models, receptor density was one of the parameters explicitly examined. Thus, for example, Land et al (1981) concluded that, when the esterase is blocked, no correlation between miniature endplate current (MEPC) amplitude and rise time is to be expected if receptor density is high, while a positive correlation is anticipated if the density is reduced.…”
Section: Methodsmentioning
confidence: 99%
“…The cell has only a brief interval in which to "capture" the growth factor, and this will depend exquisitely on the kinetics of growth factorreceptor binding. If this interval is followed by another "pulse" of growth factor, and then another, one can develop a model system in which kinetics, rather than affinity, plays the predominant role in determining timeaveraged receptor occupancy (related models have been used to describe neurotransmission at synapses [Wathey et al, 1979]). It is not known whether growth factors are released in such a pulsatile fashion, but with heparin-binding growth factors, it is likely that binding to the extracellular matrix would accelerate the removal of growth factor from solution, effectively narrowing the duration of any pulse and further enhancing the dependence of binding on kinetic, rather than thermodynamic, parameters.…”
Section: When Ligand Concentrations Change Rapidlymentioning
confidence: 99%
“…In contrast, the cojunctional compartment of G,, in particular the membranebound and secreted G, molecules concentrated around the endplates, occupy a perfect strategic position in order to very effectively remove ACh molecules diffusing away from the postsynaptic membrane (Gisiger andStephens, 1982-1983). The available data suggest that, whereas only little of the transmitter released by a single quanta1 event is able to leave the synaptic cleft (still up to 20%, according to Wathey et al, 1979; see also Rotundo and Fambrough, 1986), the amount of ACh escaping AChE molecules immobilized on junctional structures is actually far from negligible during muscle activation. Indeed, in vivo muscle stimulation is delivered in trains of rapidly succeeding impulses and an effective stimulus corresponds to a pulse of 1O-4 M ACh over a background level of about 1O-8 M (for review, see Changeux, 1981).…”
Section: Ttaincd Musclesmentioning
confidence: 99%